Early Metabolic Alterations and Predictors of Obesity Among Young Adults in Indonesia: Focus on Lipid Abnormalities and Cardiometabolic Risk - Mirasari Putri; Eva Rianti Indrasari; Yafma Femin Helta Heriady; Rizky Suganda Prawiradilaga (Faculty of Medicine Universitas Padjadjaran, 2026)
Background: The prevalence of obesity and metabolic syndrome (MetS) is rising among young adults, contributing to early cardiometabolic risk amid lifestyle transitions in Indonesia. This study examined the associations between obesity, MetS components, and body composition among Indonesian young adults.Methods: A total of 99 participants were classified based on body mass index (BMI) into normoweight (n=51) and obese (n=48) groups. Anthropometric measurements, body composition, blood pressure, and lipid profiles were assessed. MetS was defined according to the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria. Bivariate and multivariable logistic regression analyses were performed to identify factors independently associated with obesity. Results: Obesity was significantly associated with several MetS components. Abdominal obesity was observed only in the obese group (33.3%). Hypertriglyceridemia and low HDL cholesterol were more prevalent among obese participants compared with normoweight individuals (27.1% vs. 5.9% and 51.0% vs. 31.4%, respectively). MetS (≥3 NCEP ATP III criteria) was identified in 12.5% of obese participants and was absent in the normoweight group. Multivariable analysis identified family history of hypertension (adjusted OR 2.82; 95% CI 1.06–7.48) and elevated triglyceride levels (adjusted OR 4.78; 95% CI 1.13–20.22) as independent predictors of obesity.Conclusions: Obese young adults exhibit early metabolic abnormality, particularly abdominal obesity, low HDL cholesterol, and hypertriglyceridemia. Early metabolic screening and targeted preventive strategies are important to reduce future cardiometabolic risk.